Hubungan Kinerja Keuangan dengan Harga Sahani pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2007-2009 dengan Pendekatan Altman Z Score - Kartini Kartini; Reza Widhar Pahlevi (Jurnal Aplikasi Bisnis, 2017)
This empirical study intended to determine the relationship between financial performance with stock prices at the manufacturing company listed on the Indonesia Stock Exchange-year period 2007-2009 with the approach Altman Z Score.The population in this study are all listed manufac uringcompanies (listing) in Indonesia Stock Exchange during the years 2007 to 2009 (446 samples). The data was drawn from the Indonesia Stock Exchange (